Substrate type and light intensity determine lampenflora concentration on paleontological remains in show caves - Piano, Elena; Zunino, Marta; Nicolosi, Giuseppe; Pisoni, Isabella Nicole; Cimenti, Alice; Cina, Alberto; Isaia, Marco (PeerJ, 2025)
Artificial lighting in show caves is responsible for the growth of nuisance photosynthetic organisms, the so-called lampenflora, causing aesthetic, chemical and physical damage to cave cultural heritage, including paleontological resources in situ. This study focuses on the role of substrate in determining the concentration of lampenflora on paleontological findings in show caves, using the bone deposit “Cimitero degli Orsi” in the Toirano show cave (NW-Italy) as a testing ground. Specifically, we investigated whether the concentration of three distinct photosynthetic microorganisms—cyanobacteria, diatoms, and green algae—varies on different substrates, i.e., bones, rock, and soil, also keeping into account the role of light intensity. Our findings revealed that, among the tested organisms, diatoms exhibited higher concentration on bones compared to other substrates and it was even higher at increasing light intensity. On the other hand, cyanobacteria increased their concentration at increasing light without a clear preference for a specific substrate, while the presence of green algae was higher on rock and soil substrates rather than bones. When modelling the concentration of photosynthetic microorganisms within the bone deposit under different scenarios of light intensity reduction, we predicted a general decrease of all groups, that was stronger in cyanobacteria and green algae and weaker in diatoms on bone substrates. These results provide valuable insights on the colonization of nuisance photosynthetic microorganisms on bone substrates exposed to artificial lighting, with management implications for the conservation of paleontological findings in show caves.
Keywords: Tourist caves; Bone deposit; Sustainable tourism; Cave heritage; Photosynthetic microorganisms